Memorandum of Agreement Between the U.S. Air Force and the Alaska State Historic Preservation Officer Regarding the Conversion of Selected Former DEW Line Stations Submitted to the Advisory Council on Historic Preservation Pursuant to 36 CFR 800.6(a) - Willeck, Dennis G.; Bittner, Judith E.; Nissley, Claudia (611th Air Support Group, United States Air Force, 1996)
A Memorandum of Agreement (MOA) between the United States Air Force and the Alaska State Historic Preservation Office and submitted to the Advisory Council of Historic Preservation. The MOA was created to protect historic properties during the conversion of former Distant Early Warning System Line Stations, which consists of Point Lay, Point Barrow, Oliktotk and Barter Island Long Range Radar Sites.